Greater anterior cingulate activation and connectivity in response to visual and auditory high-calorie food cues in binge eating: Preliminary findings. (1st January 2016) - Geliebter, Allan; Benson, Leora; Pantazatos, Spiro P.; Hirsch, Joy; Carnell, Susan
Abstract: Obese individuals show altered neural responses to high-calorie food cues. Individuals with binge eating [BE], who exhibit heightened impulsivity and emotionality, may show a related but distinct pattern of irregular neural responses. However, few neuroimaging studies have compared BE and non-BE groups. To examine neural responses to food cues in BE, 10 women with BE and 10 women without BE (non-BE) who were matched for obesity (5 obese and 5 lean in each group) underwent fMRI scanning during presentation of visual (picture) and auditory (spoken word) cues representing high energy density (ED) foods, low-ED foods, and non-foods. We then compared regional brain activation in BE vs. non-BE groups for high-ED vs. low-ED foods. To explore differences in functional connectivity, we also compared psychophysiologic interactions [PPI] with dorsal anterior cingulate cortex [dACC] for BE vs. non-BE groups. Region of interest (ROI) analyses revealed that the BE group showed more activation than the non-BE group in the dACC, with no activation differences in the striatum or orbitofrontal cortex [OFC]. Exploratory PPI analyses revealed a trend towards greater functional connectivity with dACC in the insula, cerebellum, and supramarginal gyrus in the BE vs. non-BE group. Our results suggest that women with BE show hyper-responsivity in the dACC as well as increased coupling with other brain regions when presented with high-ED cues. These differences are independent of body weight, and appear to be associated with the BE phenotype. Highlights: We examine neural responses to visual and auditory food cues in binge eaters [BE]. BE show increased dACC responses to high vs. low-energy density [ED] cues. BE show greater dACC functional connectivity with other regions for high-ED cues. dACC hyper-responsivity and altered functional connectivity may help maintain BE.